A philosophical approach to the notion of subject in Skinner’s psychology - Castro, Marina Souto Lopes Bezerra de (Perspectivas em Análise do Comportamento, 2023)
Honoring Professor Abib’s work, this essay intends to critically present one of his texts: The subject in the labyrinth, 2007. We will investigate how the notion of Subject shows up in Skinner’s work from the philosophies and psychologies that were precursors of Radical Behaviorism. The ironic postmodern affirmation of the subject’s death reveals, in fact, a profound change in the idea that one has of the Subject. Throughout his text, Abib presents several critics, since Hume’s, to some aspects of the metaphysical view of the subject and shows how modern philosophies and psychologies already signaled the refusal of the metaphysical, transcendent, substantialist and dualist subject. When traveling through great authors, Abib presents us with dense information and surprising analyses, sometimes unusual, in his style. It passes through different notions of subject (volitional-affective-ideative process in Wundt, stream of consciousness in James, social consciousness in Mead) until reaching Skinner. In the end, there is a coherence between the modern construction of the subject and the postmodern sentence of his death. We understand, in fact, that that pre-modern subject (metaphysical, transcendent, substantial and dualist) suffered heavy blows and agonized throughout modernity, until post-modernity announced its end. However, it is not the end of the subject, but of that pre-modern subject. Abib rescues and reconstructs a consistent notion of subject with the proposals of the great authors mentioned here, leading to Skinner’s psychology. Eventually, we have a phenomenal subject, immanent to experience, non-substantial, non-dualistic and non-metaphysical.